Pengaruh Penerapan Model Belajar Kooperatif Tipe Jigsaw Oleh Guru Pak Dan Budi Pekerti Terhadap Minat Belajar Siswa Di Kelas XI SMK St. Nahanson Parapat Sipoholon Kabupaten Tapanuli Utara - Junita Mesra Wani Simaremare; Jungjungan Simorangkir; Maria Widiastuti (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to determine the effect of implementing the jigsaw type cooperative learning model in increasing students' interest in learning in PAK & Characteristics subjects at St. Vocational School. Nahanson Parapat Sipoholon, North Tapanuli Regency, 2022/2023 Academic Year. The research hypothesis is: